Analisis Pengaruh Pengalaman Kerja dan Budaya Organisasi terhadap Pengambilan Keputusan Manajerial di Rumah Sakit - Pramana, Monica; Rinawati (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
Decision-making is a critical managerial function in hospitals that determines operational success and the quality of healthcare services. This study aims to analyze the influence of work experience and organizational culture on managerial decision-making in hospital settings. An observational design with a descriptive-analytic approach was employed. The study involved hospital management staff who are directly engaged in the decision-making process. Data were collected using an open-ended questionnaire developed based on indicators of work experience and organizational culture. The findings indicate that greater work experience enhances an individual’s ability to evaluate alternatives and make effective decisions. Moreover, an organizational culture that promotes collaboration, open communication, and innovation plays an essential role in accelerating the decision-making process. In conclusion, work experience and organizational culture are key factors that significantly influence the quality of managerial decision-making in hospitals.